Analisis Perilaku Hidup Bersih dan Sehat (PHBS) Masyarakat Pesisir Kelurahan Bagan Deli Kecamatan Medan Belawan - Arifah Farhah Nasution; Arifatul Aini Asnawi; Aulina Madhani Saragih; Bella Putri Erwina; Fitriani Pramita Gurning (Universitas Batanghari Jambi, 2023)
Clean and Healthy living behaviour (PHBS) is an effort to increase the awareness of a person or group of people to care and prioritize health. Objective to analyze the clean and healthy living behavior (PHBS) of coastal communities in Bagan Deli village. This study used the Slovin data collection method and the data processing method with univariate analysis. Based on the research conducted, there were a high number of people in the Bagan Deli sub-district who did not apply PHBS. the results of the study found that the Bagan Deli village community, Medan Belawan sub-district, had not implemented 10 indicators of Clean and Healthy Life Behavior (PHBS) in their households, which caused the living environment to become dirty.